Formation of speed-strength abilities in students in the process of physical education - Zaharova, N.A.; Grigan, S.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is development of speed-strength qualities through additional exercises in the process of preparing students for passing physical standards. Methods and structure of the study. The experiment involved 100 students of DSTU aged 17-22. Students were divided into two groups: experimental and control, 50 people in each. Students in the control group trained within the standard physical education program. The experimental group trained using a program with an additional set of exercises aimed at developing speed-strength abilities. Results and conclusions. After the experiment, all five indicators of speed-strength tests in the experimental group demonstrated positive dynamics. Testing in the control group showed less positive results. In one case, negative dynamics were observed – students began running 100 meters slower by 0.3 seconds (1.8%). Also, there was no dynamics in the running high jump – still 98 cm. In the experimental group, the overall effect was significantly greater than in the control group. This indicates the success of the selected exercises and the implementation of the program for forming and developing speed-strength skills.